2021
DOI: 10.1016/j.eats.2020.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Technique for All-Inside Repair of Bucket-Handle Meniscus Tears

Abstract: Bucket-handle meniscal tears (BHMT) remain a challenge to treat due to their complex pathology and technical difficulty. Subtotal meniscectomy has shown to improve symptoms early but leads to accelerated osteoarthritis in the affected compartment and poor long-term outcomes. BHMT repair and meniscal preservation is the preferred option. This can be performed with inside-out, all-inside, or hybrid meniscus repair techniques. All-inside meniscus repair avoids the need for additional safety incisions, trained ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Yuen et al. 17 described the use of a traditional all-inside anchor-based technique for bucket-handle tears and minimized potential complications compared with inside-out techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Yuen et al. 17 described the use of a traditional all-inside anchor-based technique for bucket-handle tears and minimized potential complications compared with inside-out techniques.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that all-inside repair is quicker to perform than inside-out and that there is almost no risk of nerve entrapment, which can occur during tying of the inside-out or outside-in meniscus sutures. 10 Suturing methodologies applied in the management of meniscal tears Successful surgical meniscal repair despite surgical techniques depends on multiple factors, such as the healing process that is based on two basic principles: a solid primary fixation, and a biological process of cicatrization, which requires preceding abrasion. 11 Tears can be categorised into different categories based on healing probability and possible operative outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the additional incisions required for suture tying in "inside-out" and "outside-in" meniscus repairs heighten the risk of wound infection. 11 As no consensus on the best approach to repairing meniscus tear has been made, researchers and practitioners are calling for the development of novel repair techniques and studies that compare the performance between different techniques so that evidence-based decisions on the optimal approach can be made. 9,12…”
Section: Introductionmentioning
confidence: 99%